Context‐dependent effects of a reintroduced ungulate on soil properties are driven by soil texture, moisture, and herbivore activity. Issue 19 (7th September 2020) - Dodge, Vanessa J.; Eviner, Valerie T.; Cushman, J. Hall
Abstract: Although there is considerable evidence that large mammalian herbivores influence ecosystem‐level processes, studies have reported such widely varying results that generalizations have remained elusive. Here, we use an 18‐year‐old exclosure experiment—stratified across a landscape heterogeneous with respect to soil texture, moisture and herbivore activity—to understand the variable effects of tule elk ( Cervus canadensis nannodes ), a native reintroduced herbivore, on soil properties along the coast of northern California. Elk significantly increased soil bulk density and created a compacted layer at shallow soil depth, while decreasing infiltration rate and pH. The effects of elk on bulk density, penetration resistance, and pH varied with soil type, being least pronounced in coarse, sandy loams, and greatest in loose sand. The effects of elk on nutrient availability varied along gradients of soil texture and moisture. In coarser soils, elk decreased ammonium availability, but increased it in finer soils. Elk also decreased soil moisture content, in part through their positive effect on bulk density, and this effect was most pronounced in coarser soils. Through decreasing soil moisture content, elk also decreased nitrate availability in coarser soils. At greater levels of elk activity (as measured by dung deposition), the elk effect on bulk density was amplified, and this had a corresponding negative effect on nitrate and phosphate availability. Our study has demonstrated that a better understanding of spatial variation in the effects of herbivores on ecosystems can emerge by evaluating their influences across gradients of soil texture, soil moisture, and herbivore activity. These data enabled us to evaluate several frameworks that have been developed to understand the variable effects of herbivores on ecosystems, which is a significant step in reconciling the many competing ideas put forth to explain the context‐dependent effects of large herbivores on grazed ecosystems. Abstract : Although there is considerable evidence that large mammalian herbivores influence ecosystem‐level processes, through their effects on vegetation and disturbance regimes, studies have reported such widely varying results that generalizations have remained elusive. Using an 18‐year‐old field experiment, our research evaluates the degree to which physical characteristics of the soil and levels of herbivore activity predict context‐dependent effects of mammalian herbivores on ecosystem‐level processes.